Gendered feelings of unsafety and avoidance of local central areas in Finland 2001–2016 - Kujala Pietari (Taylor & Francis Inc., 2022)
here is a lack of knowledge about fear-of-crime-related place avoidance in Finland. International studies have examined different aspects of fear of crime and avoidance. However, examinations of the association between feelings of unsafety and place avoidance are rarer. This study takes on a less-researched perspective and examines the association between feelings of unsafety and avoidance of local central areas in Finland in 2001–2016. It conducts a gendered assessment of the association and distinguishes between different degrees of urbanization. As a methodological contribution, this study conducts cross-sectional time-series analysis. The research data consist of Finnish survey data from 2001 to 2016. The results show that levels of feelings of unsafety and avoidance in local central areas remain relatively stable during the examined period. Furthermore, the considered association is stronger among women than among men, regardless of the degree of municipality or neighbourhood urbanization. Interestingly, the strength of the considered association is more stable among women than among men. Furthermore, of all the considered independent and contextual factors, gender is the most consistently relevant factor in all areas of different degrees of urbanization. Implications of the results are discussed.